Bifurcated Chalcogen Bonds Based on One σ-Hole - Mehrparvar, Saber; Wölper, Christoph; Gleiter, Rolf; Haberhauer, Gebhard (Organic Materials, 2022)
Chalcogen bonds are noncovalent interactions and are increasingly coming into focus for the design of complex structures in research areas such as crystal engineering, molecular recognition and catalysis. Conceptionally, chalcogen bonds can be considered as interaction between one σ-hole and one Lewis base center. Herein, we analyze the interaction between bidentate chelating ligands having two nucleophilic centers with one single σ-hole of a chalcogenazole (two-lone-pair/one-σ-hole interactions). Referring to this, we show by quantum chemical calculations and X-ray studies that three bond types are possible: in the first case, a chalcogen bond is formed between the σ-hole and only one of the Lewis base centers. In the second case, a strong bond is formed by one nucleophilic center; the second center provides only a small amount of additional stabilization. In the third case, two equivalent bonds to the σ-hole are formed by both Lewis base centers. According to the calculations, the bifurcated bonds are stronger than simple chalcogen bonds and lead to a more rigid molecular arrangement in the complex.
Keywords: bifurcated bonds; chelate ligands; chalcogen bonding; DFT calculations; σ-hole